Financial Constraints and Investment Decisions of Sharia MSMEs in Indonesia: The Mediating Role of Cash Holding - Edi Pranyoto; Susanti Susanti; Ita Fionita (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Access to external financing remains one of the most critical challenges limiting the investment capacity of micro, small, and medium enterprises (MSMEs), particularly those operating under Sharia principles. While prior studies have extensively examined the relationship between financial constraints and investment decisions in large firms, limited attention has been given to the internal financial mechanisms that enable Sharia-compliant MSMEs to cope with such constraints. This study addresses this gap by examining the role of cash holding as a mediating mechanism linking financial constraints and investment decisions among Sharia MSMEs in Indonesia. Data were collected through a structured survey of 200 MSME owners or managers and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), with mediation effects assessed through bootstrapping procedures. The results reveal that financial constraints exert a significant negative effect on investment decisions (β = −0.938, p < 0.01), while simultaneously increasing cash holding (β = 0.347, p < 0.01). Cash holding, in turn, positively influences investment decisions (β = 0.643, p < 0.01) and significantly mediates the relationship between financial constraints and investment behavior (β = 0.325, p < 0.01). The structural model demonstrates strong explanatory power, with R² values of 0.932 for cash holding and 0.828 for investment decisions. These findings suggest that cash holding functions as a financial buffering mechanism that partially mitigates the adverse impact of financing constraints on MSME investment activity. By integrating financial constraints, internal liquidity management, and investment behavior within a single analytical framework, this study extends entrepreneurial finance research into the domain of Islamic MSME finance and provides practical insights for policymakers and Islamic financial institutions seeking to improve access to Sharia-compliant financing and support sustainable MSME investment.